Biology Learning Innovation in Environmental Change Materials: Approach and Method - Utari Akhir Gusti; Waliyyatu Azzahra; Ari Widodo (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
The object of learning biology is the universe and its contents. However, not all of these objects can be brought to school. One of the biological materials with these characteristics is environmental change material which is taught in class X SMA. On the other hand, teachers have attempted to design strategies to maximize learning, starting from approaches, models, methods, and media. Through biology learning innovations that integrate technology can facilitate more effective and enjoyable learning. The contextual approach with the field study method is very suitable to support learning about environmental change. Therefore, an innovation in biology learning was carried out on environmental change material. This study uses a qualitative descriptive method with data collection techniques, namely literature studies from articles from various journals, websites, and books that are relevant to the topics discussed. The results of this study are recommendations for innovative field study methods and contextual approaches in learning about environmental change with the help of technology. The use of these methods and approaches uses Google Earth technology, Class Tools, IoT, Source Net + HP Camera, Google Spreadsheets, Macroinvertebrates, LiveGap Charts, and Instagram which are expected to produce more meaningful learning.